Comprehensive Analysis of Key Genes and Regulatory Elements in Osteosarcoma Affected by Bone Matrix Mineral With Prognostic Values - Li, Mi; Jin, Xin; Li, Hao; Yang, Caihong; Deng, Sisi; Wu, Gang (Frontiers in Genetics, 2020)
Osteosarcoma is one of the most common types of bone sarcoma with a poor prognosis. However, genes involved in the mineral metabolism in the microenvironment of the bone affected by osteosarcoma are, to date, largely unknown. A public data series (GSE114237) was used to identify differentially expressed genes (DEGs) between osteosarcoma cells adhering to demineralized osseous surfaces and mineralized osseous surfaces. Functional enrichment analysis of DEGs and hub genes, protein-protein 2 interaction network of DEGs and regulatory network (miRNA-mRNA network and transcription factor (TF)-mRNA network), survival analysis of hub genes was visualized. The prognostic hub genes were considered as candidate genes and their functional predictions were analyzed. A total of 207 DEGs were mainly enriched in extracellular space and thirteen hub genes were mainly enriched in the function of epithelial to mesenchymal transition. However, out of these, only one candidate gene was found to be suitable as a candidate gene. Besides that, 297 miRNAs and 349 TFs interacting with the hub genes were screened. In conclusion, the DEGs, hub genes, miRNAs and TFs screened out in this research could contribute to comprehend the latent mechanisms in osteosarcoma affected by matrix mineral and provide potential research molecular for further study.